Donor‐derived cell‐free DNA (dd‐cfDNA) for detection of allograft rejection in pediatric kidney transplants. (20th November 2020) - Puliyanda, Dechu P.; Swinford, Rita; Pizzo, Helen; Garrison, Jonathan; De Golovine, Aleksandra M.; Jordan, Stanley C.
ABSTRACT: In pediatric transplantation, acute rejection is a major contributor of graft failure. Current approaches include kidney biopsy in response to graft dysfunction and/or the emergence of donor‐specific HLA antibodies (DSA). However, biopsy is associated with potential complications. Thus, there is a need for non‐invasive diagnostics. Detection of donor‐derived cell‐free DNA (dd‐cfDNA, AlloSure) > 1% is associated with rejection in adult kidney transplants. Here, we evaluate the utility of dd‐cfDNA for identifying allograft rejection in pediatric patients. Between 10/2017 and 10/2019, 67 patients, who underwent initial testing with dd‐cfDNA as part of routine monitoring or in response to clinical suspicion for rejection, were included. Biopsies were performed when dd‐cfDNA > 1.0% or where clinical suspicion was high. Demographics, dd‐cfDNA, antibody status, and biopsies were collected prospectively. Data were analyzed to determine predictive value of dd‐cfDNA for identifying grafts at risk for rejection. 19 of 67 patients had dd‐cfDNA testing as part of routine monitoring with a median dd‐cfDNA score of 0.37 (IQR: 0.19‐1.10). 48 of 67 patients who had clinical suspicion of rejection had median dd‐cfDNA score of 0.47 (0.24‐2.15). DSA‐positive recipients had higher dd‐cfDNA scores than those who were negative or had AT1R positivity alone ( P = .003). There was no association between dd‐cfDNA score and strength of DSA positivity. 7 of 48 recipients had a biopsy with a dd‐cfDNA score <1%; two showed evidence of rejection. Neither DSA nor AT1R positivity was statistically associated with biopsy‐proven rejection. However, dd‐cfDNA >1% was diagnostic of rejection with sensitivity of 86% and specificity of 100% (AUC: 0.996, 0.98‐1.00; P = .002). dd‐cfDNA represents a non‐invasive method for early detection of rejection in pediatric renal transplants. Our study shows dd‐cfDNA to be highly predictive of histological rejection and superior to other indicators such as graft dysfunction or antibody positivity alone. Further studies are necessary to refine these initial observations.